2019
DOI: 10.1111/jgs.15972
|View full text |Cite
|
Sign up to set email alerts
|

Frailty Is Related to Subjective Cognitive Decline in Older Women without Dementia

Abstract: OBJECTIVES Physical frailty (or loss of physiologic reserve) is associated with cognitive impairment and dementia. Subjective cognitive decline (SCD) may represent early pathologic changes of dementia. The association between these disease markers is unclear. DESIGN Cross‐sectional analysis. SETTING Community‐based participants from the Vanderbilt Memory & Aging Project. PARTICIPANTS A total of 306 older adults with normal cognition (NC; n = 174) or mild cognitive impairment (MCI; n = 132). MEASUREMENTS Frailt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 55 publications
1
26
0
2
Order By: Relevance
“…Looman and colleagues [ 15 ] also examined whether profile membership generalized across sex and reported findings that converge with our own. Previous literature suggests that there may be sex differences in the impact of frailty on cognitive aging trajectories [ 4 , 5 , 26 ]. However, we did not detect such a pattern in our data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looman and colleagues [ 15 ] also examined whether profile membership generalized across sex and reported findings that converge with our own. Previous literature suggests that there may be sex differences in the impact of frailty on cognitive aging trajectories [ 4 , 5 , 26 ]. However, we did not detect such a pattern in our data.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, these effects were moderated by sex, such that frailty change predicted the change in speed selectively for females, whereas frailty was unrelated to level or change in speed for males. At least one other study pointed to sex differences in the mechanisms linking frailty with early changes in cognitive function [ 26 ]. Given these findings and those from related research [ 27 , 28 ], we tested whether our results were robust across sex.…”
Section: Introductionmentioning
confidence: 99%
“…Frailty is a common clinical syndrome in older adults due to age-related cumulative decline in multiple physiological systems, associated with negative health outcomes, including deterioration of daily living activities, disability, institutionalization, morbidity, and mortality (1). Cross-sectional and longitudinal research has demonstrated that older adults with physical frailty exhibit poorer cognitive performance and greater risk of cognitive decline and dementia than individuals without frailty (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), and that individuals with cognitive decline or dementia show a higher risk of physical frailty (16)(17)(18). It has also been demonstrated that the coexistence of physical frailty and cognitive impairment (cognitive frailty), ranging from 1 to 5% in community-dwelling older adults (19), increases the risk of mortality (20)(21)(22)(23)(24)(25), functional disability (26), and incident neurocognitive disorders (9,27) in later life.…”
Section: Introductionmentioning
confidence: 99%
“…Frailty was closely associated with SCD long before manifestation of objective cognitive impairment. 35 Especially, subjective complaints in mathematic reasoning were highly associated with frailty. 36 Smokers in SCD group in our study was likely to have been exposed to increased chance of frailty than their NC counterpart.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this increase in risk of falls or fracture in SCD could be attributed to additive role of frailty on harmful effects of smoking. Frailty was closely associated with SCD long before manifestation of objective cognitive impairment [ 35 ]. Especially, subjective complaints in mathematic reasoning were highly associated with frailty [ 36 ].…”
Section: Discussionmentioning
confidence: 99%